The Use of the Enterprise Discounted Cash Flow Method in Determining the Intrinsic Price of Stock a Case Study at PT. Aneka Tambang, Tbk 2017-2023 Period - Indah Rosiana Wati; Dudi Rudianto (Sean Institute, 2025)
This study aims to determine the intrinsic value of PT Aneka Tambang Tbk (ANTM) shares using the Enterprise Discounted Cash Flow (DCF) method during the period from 2017 to 2023. The Enterprise DCF method is a fundamental valuation approach that calculates the company's value based on historical free cash flows, which are then discounted to their present value using the Weighted Average Cost of Capital (WACC). This research uses a descriptive quantitative approach with historical data and no forward-looking projections to ensure the objectivity and validity of the valuation results. The findings show fluctuations in the intrinsic value of ANTM shares during the 2017–2023 period, reflecting macroeconomic dynamics and other factors. By comparing the intrinsic value and the market price of ANTM shares, this study concludes that the stock was undervalued in 2019 and 2023, and overvalued in 2017 and 2018. This study emphasizes the importance of fundamental analysis based on historical data as a basis for conservative and data driven investment decision-making.